Magnetic Seizure Therapy for Suicidality in Treatment-Resistant Depression - Weissman, Cory R. (JAMA Netw Open, 2020)
IMPORTANCE: There is an unmet need for effective treatments for suicidality in mental disorders. Magnetic seizure therapy (MST) has been investigated as an alternative to electroconvulsive therapy, a known effective treatment for suicidality, in the management of treatment-resistant major depressive disorder, with promising findings. Yet, there are very limited data on the association of MST with suicidality directly. It is important to explore the potential of MST as a viable treatment alternative to electroconvulsive therapy for suicidality. OBJECTIVE: To determine the association of MST with suicidality in patients with treatment-resistant major depressive disorder. DESIGN, SETTING, AND PARTICIPANTS: This nonrandomized controlled trial took place at a single tertiary care psychiatric facility in Canada. It followed an open-label study design with consecutive treatment cohorts. Consecutive groupings of 67 patients with treatment-resistant major depressive disorder and with baseline suicidality present were treated for up to 24 treatments. The study was run from February 2012 through June 2019. Patients were followed up for 6 months at the end of the treatment period. This post hoc secondary analysis of the trial was performed from January to November 2019. INTERVENTIONS: MST was delivered at 100% stimulator output over the prefrontal cortex with low (25 Hz), moderate (50 or 60 Hz), or high (100 Hz) frequency, for a maximum of 24 sessions. MAIN OUTCOMES AND MEASURES: Remission from suicidality was measured as an end point score of 0 on the Beck Scale for Suicidal Ideation. A linear mixed model was used to assess the trajectory of Beck Scale for Suicidal Ideation scores. RESULTS: A total of 67 patients (mean [SD] age, 46.3 [13.6] years; 40 women [60.0%]) received a mean (SD) of 19.5 (5.1) MST treatments. The overall number of patients achieving remission was 32 (47.8%). Sixteen patients (55.2%) receiving low-frequency MST achieved remission, as well as 12 patients (54.5%) in the moderate-frequency group, and 4 patients (25.0%) in the high-frequency group. The linear mixed model revealed an association of time with Beck Scale for Suicidal Ideation scores (F(8,293.95) = 5.73; P < .001). CONCLUSIONS AND RELEVANCE: These findings suggest that MST may be an effective treatment for suicidality, and sensitivity analysis shows this may be particularly so at low and moderate frequencies. Future studies should directly compare MST with electroconvulsive therapy for treating suicidality and should evaluate MST as a treatment for suicidality across mental disorders. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01596608